Serine, N-acetylaspartate differentiate adolescents with juvenile idiopathic arthritis compared with healthy controls: a metabolomics cross-sectional study - Lewis, Kimberly A.; Osier, Nico; Carrasco, Ruy; Chiou, Jennifer; Carter, Patricia; Garcia, Alexandra; Flowers, Elena; Gennatas, Efstathios D.; Nguyen, Christina; Rana, Ambreen; Brown, Sharon A.; Tiziani, Stefano (Pediatric rheumatology online journal, 2022)
Background In comparison with the general population, adolescents with juvenile idiopathic arthritis (JIA) are at higher risk for morbidity and mortality. However, limited evidence is available about this condition’s underlying metabolic profile in adolescents with JIA relative to healthy controls. In this untargeted, cross-sectional metabolomics study, we explore the plasma metabolites in this population. Methods A sample of 20 adolescents with JIA and 20 controls aged 13–17 years were recruited to complete surveys, provide medical histories and biospecimens, and undergo assessments. Fasting morning plasma samples were processed with liquid chromatography–mass spectrometry. Data were centered, scaled, and analyzed using generalized linear models accounting for age, sex, and medications ( p -values adjusted for multiple comparisons using the Holm method). Spearman’s correlations were used to evaluate relationships among metabolites, time since diagnosis, and disease severity. Results Of 72 metabolites identified in the samples, 55 were common to both groups. After adjustments, 6 metabolites remained significantly different between groups. Alpha-glucose, alpha-ketoglutarate, serine, and N -acetylaspartate were significantly lower in the JIA group than in controls; glycine and cystine were higher. Seven additional metabolites were detected only in the JIA group; 10 additional metabolites were detected only in the control group. Metabolites were unrelated to disease severity or time since diagnosis. Conclusions The metabolic signature of adolescents with JIA relative to controls reflects a disruption in oxidative stress; neurological health; and amino acid, caffeine, and energy metabolism pathways. Serine and N -acetylaspartate were promising potential biomarkers, and their metabolic pathways are linked to both JIA and cardiovascular disease risk. The pathways may be a source of new diagnostic, treatment, or prevention options. This study’s findings contribute new knowledge for systems biology and precision health approaches to JIA research. Further research is warranted to confirm these findings in a larger sample.